Social movements in islamic contexts: anthropological approaches - Silva,Maria Cardeira da (2006)
I will present, very briefly, some of the main approaches within social sciences, and particularly anthropology, which have contributed to elucidate social movements in Islamic contexts. This is specifically intended to provide a general overview, in order to more easily situate the following presentations. This also aims to better integrate those readers less familiarized with the anthropological jargon and current debates on these subjects. I will give particular importance to ethnographic research and its relevant role in preventing or refraining essentialist conclusions and considerations on matters of such political relevance. I will also highlight the authors who have used their ethnographies in order to try to solve the current dilemma between political and analytical approaches, a dilemma that is a frequent source for misunderstandings on these topics.